Relações humanas com a água : percepção ambiental, saberes tradicionais, simbolismos culturais e contribuições para a gestão e conservação da água - Dictoro, Vinicius Perez (2016)
For many centuries, mankind has considered fresh water as inextinguishable feature, without evaluating the environmental consequences related to quantity and quality. The current form of appropriation of water to meet the high demand of the various uses of water resources by the company has configured intense transformations in human relations with the water. In the old days, companies had other complementary visions to the direction of the water deities, bows and very natural available both for human existence and other species, as to the balance and maintenance of ecosystems. Therefore, human relations with the water permeate this relationship of utilitarian sense, only for economic purposes and survival, and configure other relationships as: religious, cultural, symbolic and emotional. In this way, the overall objective of the research was to identify and analyze different human relationships with water, seeking to understand the varied forms of recovery of water, and also to analyze the current model of water management through National Water Resources Policy instruments, for the purpose of providing subsidies that may assist in the consideration of human relationships with water in its management and conservation. This was followed by work based on qualitative research and case study was developed in two distinct audiences, residents of Pirapora-MG, situated on the banks of the São Francisco River, and members of river basin committees. The data were collected through interviews and questionnaires. Symbolic, cultural relations were identified, mystical and local knowledge, affective of individuals with the water. These aspects should be transmitted in new forms of awareness for the management and conservation of water. It is necessary to step up the way of acting on awareness, promote new programs and new actions with the purpose of expanding the vision centered on Man and on their anthropogenic activities, enabling a rescue of cultural symbolism of the water and the various relationships and appreciation that it has with society.